Integrating people with disabilities into society, and preventing disability in light of Islamic teachings - Weiss, Hajar Ismail (Sulaimani Journal for Humanities, 2025)
The research aims to identify the most important Islamic teachings and guidelines contained in the Holy Qur'anic verses and the noble Prophetic hadiths that urge the integration of people with disabilities into society and the prevention of disability, mentioning its causes, types, and ways to reduce and minimize it. The study included two sections in which we talked about the definition of disability, its types, causes, and its forms mentioned in the Holy Qur'an, and the definition of people with disabilities and people with special needs and the difference between them, and the most important teachings and preventive measures to reduce disability from its Sharia perspective, and to reach results that prove Islam's care for the human being and its concern for his safety and protection from disability and everything that harms him or stands in the way of his humanity and his physical, mental, intellectual, and motor perfection, etc
Keywords: Community; Integration; Prevention; Disability; Islamic; Teachings